Breakout - Messner, Kate (New York : Bloomsbury, 2018)
From multiple perspectives, tells of a time capsule project and the middle schoolers who contribute, including future journalist Nora Tucker and newcomer Elidee Jones, whose brother is in the local prison.
Keywords: Time capsules -- Fiction; Community life -- Fiction; Journalism -- Fiction; Prisons -- Fiction; Schools -- Fiction; Community life -- Fiction; Journalism -- Fiction; Prisons -- Fiction; School stories